2017
DOI: 10.3102/0162373717693108
|View full text |Cite
|
Sign up to set email alerts
|

Vouchers in the Bayou: The Effects of the Louisiana Scholarship Program on Student Achievement After 2 Years

Abstract: The Louisiana Scholarship Program (LSP) offers publicly funded vouchers to students in low-performing schools with family income no greater than 250% of the poverty line, allowing them to enroll in participating private schools. Initially established in 2008 as a pilot program in New Orleans, the LSP was expanded statewide in 2012. This article examines the experimental effects of using an LSP scholarship to enroll in one’s first-choice private school on student achievement in the first 2 years following the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 25 publications
3
42
3
Order By: Relevance
“…Third, we examined the effects of a voucher program that operates within a different context from other programs, whereby many private schools were participating in statewide testing prior to the implementation of the voucher program. Finally, unlike other statewide studies that cover a shorter time frame (Abdulkadiroglu, Pathak, & Walters, ; Figlio & Karbownik, ; Mills & Wolf, ), we examined the impact for students who have received a voucher to attend private schools up to four years.…”
Section: Introductionmentioning
confidence: 99%
“…Third, we examined the effects of a voucher program that operates within a different context from other programs, whereby many private schools were participating in statewide testing prior to the implementation of the voucher program. Finally, unlike other statewide studies that cover a shorter time frame (Abdulkadiroglu, Pathak, & Walters, ; Figlio & Karbownik, ; Mills & Wolf, ), we examined the impact for students who have received a voucher to attend private schools up to four years.…”
Section: Introductionmentioning
confidence: 99%
“…This latter test complements work by Mills and Wolf (2017) that attempts to shed light on the issue of potential "test familiarity bias" in the context of a rigorously designed evaluation of the Louisiana Scholarship Program. By taking advantage of the fact that different grade levels relied on different accountability assessments in some years, some of which were more aligned with the state curriculum than others, Mills and Wolf decompose the negative impact of Louisiana's voucher program to identify what proportion of that impact can be attributed to the specific assessment used.…”
mentioning
confidence: 85%
“…Proposals to subsidize private education can be traced back to John Stuart Mill (1869), who argued that compulsory education should be compelled by the state but not provided by that entity. To avoid the inevitable conflicts that would arise over what should be taught and how, Mill proposed breaking the financing of education from its provision.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The first experimental evaluations in the world to find negative effects of a private school choice program on student achievement were of the Louisiana voucher program (Abdulkadiroğlu, Pathak, and Walters, ; Mills, ; Mills and Wolf, , ). Abdulkadiroğlu, Pathak, and Walters () found that lower‐quality private schools—as measured by student enrollment—were more likely to participate in the Louisiana Scholarship Program (LSP).…”
Section: Literature Reviewmentioning
confidence: 99%